Observation of isomorphic phase transition in non-perovskite Green CsSnI 3 - Bharti P.C.; Jha P.K.; Jha P.A.; Singh P. (My University, 2025)
The green polymorph of CsSnI3 synthesized by cold-sintering method with cubic phase at 295(±1) K is found. The structural refinement shows the cubic Th(m-3)-Pa3¯ phase with paramorphic hemihedry (diacisdodecahedery) for CsSnI3. The determined lattice constants with s.u. values are a = 12.2771(1) Å with cell volume = 1850.49(4) Å3. The Iodine atoms do not occupy the equivalent positions and the number of molecules per unit cell is 8. Contrary to other colour polymorphs, this green CsSnI3 has shown successive isomorphic phase transitions in accordance with the group–subgroup theory. © 2022 Acta Materialia Inc.